Selumetinib for symptomatic, inoperable plexiform neurofibromas in children with neurofibromatosis type 1: A national real‐world case series. Issue 8 (15th March 2022) - Coltin, Hallie; Perreault, Sébastien; Larouche, Valérie; Black, Karina; Wilson, Bev; Vanan, Magimairajan Issai; Gupta, Abha A.; Morgenstern, Daniel A.; Parkin, Patricia C.; Bouffet, Eric; Ramaswamy, Vijay
Abstract: Neurofibromatosis type 1‐associated plexiform neurofibromas can cause debilitating symptoms and be life threatening. Treatment options are limited, given their tendency to regrow following surgery and their propensity to transform into malignant tumours following radiation. Selumetinib is an oral selective inhibitor of RAS‐mitogen‐activated protein kinase (MAPK) 1 and 2, which has shown efficacy for tumour shrinkage/stabilisation and symptom improvement. We report a national case series of 19 children treated with selumetinib. All patients experienced symptom improvement or stabilisation with an acceptable toxicity profile, including those patients previously treated with trametinib. This real‐world experience confirms previous trials showing significant clinical benefit for this patient population.